Salmonella Bacterin Vaccination Decreases Shedding and Colonization of Salmonella Typhimurium in Pigs - Eduarda Alexandra Gonçalves de Oliveira Moura; Daniela Gomes da Silva; Caio Henrique Turco; Thainara Vitoria Carnevalli Sanches; Gabriel Yuri Storino; Henrique Meiroz de Souza Almeida; Marina Lopes Mechler-Dreibi; Isabela Peixoto Rabelo; Karina Sonalio; Luís Guilherme de Oliveira (Microorganisms, 2021)
Since the occurrence of swine salmonellosis has increased over time and control strategies other than biosecurity are highly recommended, the present study aimed to evaluate the efficacy of vaccination with Salmonella Choleraesuis and Salmonella Typhimurium bacterins in pigs. Two experimental groups were formed: G1, animals immunized with two doses of a commercial vaccine (n = 20); G2, control group (n = 20). After vaccination, all pigs were orally challenged (D0) with 108 CFU of Salmonella Typhimurium and evaluated for 40 days. Every 10 days after D0, five piglets from each experimental group were euthanized and submitted to the necroscopic examination, when organ samples were collected. Blood samples and rectal swabs were collected before the first dose of the vaccine (D−42), before the second dose (D−21), before the challenge (D0), and thereafter, every three days until D39. Blood count, serum IgG measurement by ELISA, and the excretion of Salmonella Typhimurium in feces were evaluated. While the results from blood count and serum IgG concentration did not differ, the detection and excretion of Salmonella between G1 and G2 differed (p < 0.05). Therefore, it was observed that this vaccine partially protected the animals against experimental infection with Salmonella Typhimurium, reducing the excretion of bacteria in feces.